Hemangiopericytoma of the gingiva - An exemplary differential of a masquerading tumor - ManoVijay Balagangadharan; Mathew Jacob; Sekar Bala; Arulmani Periasamy (Wolters Kluwer Medknow Publications, 2022)
Periodontal diseases are unique as a small number lesions appearing as inflammatory in reality are neoplastic in nature, and it is imperative that an accurate diagnosis be rendered to provide the appropriate treatment and management. One of the most common clinical presentations of gingival lesions is pedunculated soft-tissue swellings. We report the case of a 63-year-old female who presented with a painless swelling on the interdental papilla of 23 and 24 with a history of recurrences. The lesion was excised by wide surgical excision. This article presents a unique case of a vascular tumor that had clinically mimicked a reactive lesion and with detailed history, thorough clinical examination had provided clues to a vascular entity namely hemangiopericytoma which was confirmed by histological diagnosis. Oral lesions, particularly occurring in gingiva, most often appear clinically benign or innocuous thus necessitating the need for careful examination with investigations to render a diagnosis.